2022
DOI: 10.1038/s42003-022-03104-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt with nitric oxide deficiency induces nocturnal polyuria in mice via hyperactivation of intrarenal angiotensin II-SPAK-NCC pathway

Abstract: Nocturnal polyuria is the most frequent cause of nocturia, a common disease associated with a compromised quality of life and increased mortality. Its pathogenesis is complex, and the detailed underlying mechanism remains unknown. Herein, we report that concomitant intake of a high-salt diet and reduced nitric oxide (NO) production achieved through Nω-Nitro-L-arginine methyl ester hydrochloride (L-NAME) administration in mice resulted in nocturnal polyuria recapitulating the clinical features in humans. High s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The freely diffusible gaseous compound NO is an important messenger in many organ systems, particularly the CNS [ 56 ]. Earlier studies also suggested high salt intake can reduce NO production in different cell types [ 31 , 57 ]. However, exposure to a 3:1 and 1:1 combination of NaCl and CH 3 COONa-treated microglial media in neuronal cells showed an increase in nitric oxide (NO) production in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The freely diffusible gaseous compound NO is an important messenger in many organ systems, particularly the CNS [ 56 ]. Earlier studies also suggested high salt intake can reduce NO production in different cell types [ 31 , 57 ]. However, exposure to a 3:1 and 1:1 combination of NaCl and CH 3 COONa-treated microglial media in neuronal cells showed an increase in nitric oxide (NO) production in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a deficiency of nitric oxide can lead to either sodium retention or sodium wasting, possibly depending on the specific tubular location and timing (nitric oxide has a short half-life). [107][108][109] Deficiency of nitric oxide is a hallmark of some mitochondrial diseases, 110 and it is likely to be present in other mitochondrial diseases as well because of the production of reactive oxygen species. 107 Hypothetically, different mitochondrial defects might have different effects on the production of reactive oxygen species and nitric oxide, depending on the cell type and its unique metabolic wiring, and thereby differ in the effect on electrolyte reabsorption.…”
Section: A B Cmentioning
confidence: 99%
“…They contribute to understanding of the mechanisms for erection such as the signal cascade of nitric oxide synthase (NOS)‐cGMP axis 8 . Generally, recent urological research showed significant advances in the research field for NO signal and local neuronal regulation 9,10 . There are growing concerns about pathological mechanisms of ED and the effect of aging on the erectile structure including fibrosis and aberrant chondrogenesis 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…research field for NO signal and local neuronal regulation. 9,10 There are growing concerns about pathological mechanisms of ED and the effect of aging on the erectile structure including fibrosis and aberrant chondrogenesis. 11,12 However, analyses of such pathological changes inside the erectile system, the sinusoids has rarely been studied through only a few histological studies.…”
mentioning
confidence: 99%